2020
DOI: 10.1371/journal.pone.0235998
|View full text |Cite
|
Sign up to set email alerts
|

Replication stress and FOXM1 drive radiation induced genomic instability and cell transformation

Abstract: In contrast to the vast majority of research that has focused on the immediate effects of ionizing radiation, this work concentrates on the molecular mechanism driving delayed effects that emerge in the progeny of the exposed cells. We employed functional protein arrays to identify molecular changes induced in a human bronchial epithelial cell line (HBEC3-KT) and osteosarcoma cell line (U2OS) and evaluated their impact on outcomes associated with radiation induced genomic instability (RIGI) at day 5 and 7 post… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 91 publications
(127 reference statements)
1
10
0
Order By: Relevance
“…FOXM1 and RHNO1 co-expression may increase tumor resiliency by allowing tumor cells to gain a fitness advantage of increased growth and proliferation without accumulating excessive DNA damage. Consistently, FOXM1-expressing tumors are highly enriched for biomarkers of RS ( Li et al, 2020 ). Therapeutic targeting of the FOXM1/RHNO1 bidirectional gene unit may be accomplished using inhibitors of FOXM1 and/or ATR/Chk1/WEE1.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…FOXM1 and RHNO1 co-expression may increase tumor resiliency by allowing tumor cells to gain a fitness advantage of increased growth and proliferation without accumulating excessive DNA damage. Consistently, FOXM1-expressing tumors are highly enriched for biomarkers of RS ( Li et al, 2020 ). Therapeutic targeting of the FOXM1/RHNO1 bidirectional gene unit may be accomplished using inhibitors of FOXM1 and/or ATR/Chk1/WEE1.…”
Section: Discussionmentioning
confidence: 91%
“…Critical support for this model is provided by a recent study that demonstrated that FOXM1 expression induced RS and genomic instability in bronchial epithelial cells and U2OS cells ( Li et al, 2020 ). Additionally, the authors showed that FOXM1 expression correlates with RS biomarkers in The Cancer Protein Atlas data from several cancer types, including HGSC ( Li et al, 2020 ). We thus hypothesize that the mechanistic link between FOXM1 and RHNO1 centers around RS, in that RHNO1 may help to mitigate excessive RS driven by FOXM1 ( Figure 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA replication stress (RS) is caused by extrinsic and intrinsic factors that disrupt replication fork dynamics, and critically, RS is a major driver of cancer genomic instability [ 307 , 308 ]. Notably, FOXM1 was recently reported to induce DNA replication stress in vitro and FOXM1 expression was observed to correlate with expression of RS biomarkers in several cancer types, including HGSC [ 309 ]. Our recent study also suggests a link between FOXM1 and RS.…”
Section: Foxm1 Oncogenic Functionsmentioning
confidence: 99%
“…FoxM1 played an important role in DNA replication. FoxM1 was recently reported to induce DNA replication pressure in vitro, and FoxM1 expression was observed to be associated with the expression of DNA replication pressure biomarkers in several cancer types 30 . In order to evaluate the role of FoxM1 in DNA replication of lung adenocarcinoma cells, we further analyzed the transcriptional regulation of related differential genes in DNA replication pathway.…”
Section: Discussionmentioning
confidence: 98%